Dexmedetomidine-isoflurane versus fentanyl-isoflurane anesthesia for colorectal surgery: Effect on perianastomotic microperfusion and oxygenation in pigs - Mynar, Marian; Dusek, Tomas; Subrt, Zdenek; Turek, Zdenek (Clinical hemorheology and microcirculation, 2025)
BACKGROUND: The effect of dexmedetomidine on regional splanchnic blood flow remain unclear. OBJECTIVES: We hypothesized, that there is no difference in regional rectal perianastomotic perfusion and oxygenation when using non-opioid dexmedetomidine-isoflurane anesthesia when compared to fentanyl-isoflurane anesthesia. METHODS: Ten female pigs were randomly divided into two groups (Dexmedetomidine, DEX, Fentanyl, FNT). Analgesia was provided by either dexmedetomidine (0.7-1.0 μg/kg/h) or fentanyl (6-10 μg/kg/h). The model of rectosigmoid resection in pigs was used. Two combined Laser Doppler flowmetry (LDF) and oxymetry probes were fixed on the antimesenterial site of the rectosigmoid, one orally and the second distally to resection zone. At the end of the experiment all animals were woken up and extubated. The healing of the anastomosis was controlled seven days after the operation. RESULTS: All experimental animals were hemodynamically stable throughout the experiment. No anastomotic leakage was detected. All animals survived until the seventh postoperative day. In the DEX group the median of the LDF signal on aboral site at the end of experiment was 35% (23-49%), in FNT group the median of the LDF signal was 19% (12-28%), which was statistically significantly lower (p < 0,05). CONCLUSIONS: This study has shown some protective effects of dexmedetomidine-isoflurane based anesthesia on perianastomotic microcirculation when compared to fentanyl-isoflurane based anesthesia.
Keywords: Animals; mikrocirkulace; Female; Dexmedetomidine; dexmedetomidin; Colorectal Surgery; ženské pohlaví; Fentanyl; anastomóza chirurgická; kolorektální chirurgie; prasata; laser Doppler flowmetry; Swine; Oxygen; Anastomosis, Surgical; regional splanchnic perfusion; Microcirculation; colorectal surgery; zvířata; fentanyl; kyslík